ASUHAN KEPERAWATAN KELUARGA TAHAP PERKEMBANGAN REMAJA DENGAN INTERVENSI TERAPI UAP AIR HANGAT DAN MINYAK KAYU PUTIH TERHADAP KELANCARAN JALAN NAFAS PADA ANAK DENGAN ISPA - Nuryatul Hasanah; Rina Puspita Sari; Hasan Basri (Nusantara Hasana Journal, 2024)
The family is the most basic social contract for producing quality humans. Changes at each stage of family development are followed by changes in family tasks based on the functions they have. Children are the age group most vulnerable to disease, this is related to the child's protective function or immunity, one of the diseases often suffered by children aged 3-6 years is respiratory problems or respiratory infections. Based on data on the 10 most common diseases at the Priuk Jaya Community Health Center, ISPA is the disease most suffered by the people of Priuk Jaya with a total of 554 cases in October 2023. One of the treatments that can be done to treat ISPA is simple steam therapy with warm water and eucalyptus oil. This scientific paper aims to provide family care for the adolescent development stage of ISPA children. Providing a nurturing intervention with the innovation of warm water steam therapy and eucalyptus oil to facilitate airways in children with ISPA, which was carried out for 7 days. Based on the case study, after 7 days of treatment and the assistance of pharmacological therapy, the results showed that the airway was smooth, such as no phlegm, no rhonchi, respiratory frequency within normal limits in children. After carrying out moisturizing procedures using warm water vapor and eucalyptus oil for 7 days, An S's respiratory frequency decreased from 35x/minute to 23x/minute.